A re-visitation to reported results on optical solitons. (August 2020) - Kumar, Sachin; Malik, Sandeep; Biswas, Anjan
Highlights: Provide the generalized symmetries of equations considered in the some of recent published papers on optical solutions. Generalized symmetries for Kundu–Mukherjee–Naskar equation and nonlocal-parabolic combo nonlinearity also provided. Corresponding to Kundu–Mukherjee–Naskar equation and nonlocal-parabolic combo nonlinearity some new exact solutions are also presented. Abstract: This corrigendum is to provide the generalized symmetries of equations considered in the some of recent published papers. Also, corresponding to the generalized symmetries for Kundu–Mukherjee–Naskar equation and nonlocal-parabolic combo nonlinearity, some new exact solutions are also presented.